Analisis Pengaruh Fraud Triangle pada Kecurangan Laporan Keuangan PT Timah tahun 2018 - Khellyn Vaustine; Budi Harsono Budi Harsono; Jolin Floren Elvinis; Xaviolyn (LPPM Universitas Putera Batam, 2022)
This study aims to analyze the presence of financial statement fraud that has been presented by PT Timah Tbk. The trigger factor for this fraud is the fraud triangle which can be divided into three, namely pressure, opportunity, and rationalization. In 2018, PT Timah was suspected of processing its financial reports, especially in the profit section. This action is not in accordance with the Financial Accounting Standards (SAK) that apply in Indonesia. This has attracted the attention of researchers to analyze what factors trigger PT Timah to commit fraud in its financial statements. This study analyzes the fraud triangle factor in PT Timah's 2018 financial statements using qualitative and quantitative research methods. The results showed that there was pressure for PT Timah to capture profits and expenses, there was an opportunity for PT Timah to commit fraud due to ineffective supervision, and there was an intention to rationalize its audit opinion.